2022
DOI: 10.3847/psj/ac6bef
|View full text |Cite
|
Sign up to set email alerts
|

New Polarimetric Data for the Galilean Satellites: Europa Observations and Modeling

Abstract: This paper is dedicated to a long-standing problem of the shape of the negative branch of polarization (NBP) for Jupiter's moon Europa, determination of which is crucial for the characterization of the icy regolith on this satellite and similar objects, as well as for further progress in understanding light scattering by particulate surfaces. To establish the shape of Europa's NBP, in 2018–2021 we accomplished high-precision disk-integrated polarimetry of Europa in the UBVR I bands using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…A detailed description of the instrumentation, the method of polarization measurements of satellites and sky background, and the calculation of polarization parameters can be found in the paper by Kiselev et al (2022). The results of our current measurements of the polarization of Io and Ganymede in the UBVRI bands are summarized in the Appendix (Tables A1 and A2).…”
Section: New Observations Instrumentation and Data Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed description of the instrumentation, the method of polarization measurements of satellites and sky background, and the calculation of polarization parameters can be found in the paper by Kiselev et al (2022). The results of our current measurements of the polarization of Io and Ganymede in the UBVRI bands are summarized in the Appendix (Tables A1 and A2).…”
Section: New Observations Instrumentation and Data Reductionmentioning
confidence: 99%
“…For this, we used the identical two-channel photoelectric polarimeters mounted on the 2.6 m Shajn reflector of the Crimean Astrophysical Observatory and the 2 m telescope of the Peak Terskol Observatory. In the study by Kiselev et al (2022), it was found that the NPB for Europa is a highly asymmetric curve with a sharp polarization minimum P min ≈ −0.3% at phase angle α min 0°.4, after which the polarization degree gradually increases to positive values, passing the inversion angle at α inv ≈ 6°-7°.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations